2020
DOI: 10.1530/eje-19-0684
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of ghrelin, des-acyl ghrelin and LEAP2 in children with obesity: correlation with age and insulin resistance

Abstract: Objective The octanoylated peptide hormone ghrelin regulates appetite and glycaemic control. Des-acyl ghrelin abolishes some effects of ghrelin, but does not bind to ghrelin receptor. LEAP2 is a novel ligand for ghrelin receptor that blocks the effects of ghrelin. Some evidences show that plasma levels of these peptides are altered in adults with obesity, but their levels in childhood obesity remain poorly studied. Therefore, the objective of this study was to assess fasting plasma levels of ghrelin, des-acyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 40 publications
5
28
2
2
Order By: Relevance
“…GHRH+arginine stimulation tests were repeated twice in idiopathic aGHD to confirm if they truly had aGHD. Median and interquartile range age of the group was 53 (41–57) years, while BMI was 27.1 25–35 kg/m 2 , as expected due to the features of the syndrome. Group B, Healthy Controls (15 patients, 10 females and 5 males). Median and interquartile range age was 47 (36–57) years, while BMI 22.9 (20.8–33.1) kg/m 2 .…”
Section: Methodssupporting
confidence: 63%
“…GHRH+arginine stimulation tests were repeated twice in idiopathic aGHD to confirm if they truly had aGHD. Median and interquartile range age of the group was 53 (41–57) years, while BMI was 27.1 25–35 kg/m 2 , as expected due to the features of the syndrome. Group B, Healthy Controls (15 patients, 10 females and 5 males). Median and interquartile range age was 47 (36–57) years, while BMI 22.9 (20.8–33.1) kg/m 2 .…”
Section: Methodssupporting
confidence: 63%
“…Moreover, LEAP2 correlated positively with age, BMI, WHR, MRI-PDFF and FibroScan-CAP, which are also consistent with the Mani's report [9] (positive correlation with BMI, body fat and visceral fat). However, the opposite results (inverse correlation with BMI) were reported by Fittipaldi et al [41] in obese children (a cross-sectional cohort) and by Aslanipour et al [42] in women with PCOS (an age-and BMI-matched case-control study). The controversial phenomena may relate to specific population and study design.…”
Section: Controlmentioning
confidence: 71%
“…Besides Mani's study [9], there are two other studies evaluated circulating LEAP2 in humans. Fittipaldi et al [41] reported decreased plasma levels of LEAP2 in overweigh/obese children of 3-12 years old. Polycystic ovary syndrome (PCOS) is a reproductive disease connects closely to metabolic disorders, e. g. insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Варто було б очікувати підвищеного рівня греліну в пацієнтів даної категорії. Проте, згідно з даними наукової літератури, рівень ацетильованого греліну, навпаки, знижується в пацієнтів з ожирінням, ЦД 2-го типу та метаболічним синдромом [45,46], що пов'язують із фізіологічною адаптацією організму до позитивного енергетичного балансу, який виникає при ожирінні [47][48][49].…”
Section: кп -unclassified